The Lubanga Case dictated by the International Criminal Court and its scope for vulnerable children: lessons learned ten years later - Chacón Mata, Alfonso (2025)
This essay aims to establish a retrospective analysis of the Thomas Lubanga ruling in the International Criminal Court, showing some lessons that this precedent has left us for children participating in war conflicts.